2018
DOI: 10.1161/circep.118.006182
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial of Surgical Versus Catheter Ablation for Paroxysmal and Early Persistent Atrial Fibrillation

Abstract: Background: Current guidelines recommend both percutaneous catheter ablation (CA) and surgical ablation in the treatment of atrial fibrillation, with different levels of evidence. No direct comparison has been made between minimally invasive thoracoscopic pulmonary vein isolation with left atrial appendage ligation (surgical MIPI) versus percutaneous CA comprising of pulmonary vein isolation as primary treatment of atrial fibrillation. We, therefore, conducted a randomized controlled trial comparin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
43
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 20 publications
0
43
1
1
Order By: Relevance
“…Second, TA also had higher rates of adverse events particularly thoracic complications. The key clinical characteristics of eligible randomized trials include middle‐aged patients with a high prevalence of paroxysmal AF in 85%, AF duration of 5.9 years, high antiarrhythmic use in 95%, prior failed CA in approximately half, and normal mean left ventricular ejection fraction, but mildly dilated left atrial dimensions on echocardiography 7–12 . Therefore, patients with paroxysmal AF refractory to antiarrhythmic drugs and previous failed CA, but with preserved left ventricular function, are those that our findings best apply to.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Second, TA also had higher rates of adverse events particularly thoracic complications. The key clinical characteristics of eligible randomized trials include middle‐aged patients with a high prevalence of paroxysmal AF in 85%, AF duration of 5.9 years, high antiarrhythmic use in 95%, prior failed CA in approximately half, and normal mean left ventricular ejection fraction, but mildly dilated left atrial dimensions on echocardiography 7–12 . Therefore, patients with paroxysmal AF refractory to antiarrhythmic drugs and previous failed CA, but with preserved left ventricular function, are those that our findings best apply to.…”
Section: Discussionmentioning
confidence: 79%
“…Furthermore, the lower rate of repeat ablation during follow‐up (25% vs 2%) is another distinct advantage of TA. However, the high adverse event rates in up to 25% of TA even in randomized trials is important, observed across four of five studies reporting this 7,8,10,11 . In particularly, thoracic complications much higher in TA are detrimental because of their frequent need of invasive procedures, prolonging of intensive care and/or hospital stay, and potential for long‐term sequelae.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, highly selected patients with less amendable factors related to AF may be good candidates of AF surgery 93). However, recent randomized controlled trial failed to show superior efficacy of minimally invasive thoracoscopic PV isolation with LA appendage ligation compared to catheter ablation in spite of significantly higher complication rate 94)…”
Section: Surgical Atrial Fibrillation Ablationmentioning
confidence: 99%
“…This is reported to be the first direct comparison of a catheter-based technique to a thoracoscopic surgical technique for primary ablation of paroxysmal and recent onset persistent atrial fibrillation. 11 The majority of previous studies into surgical ablation had required patients to have had a failed catheter ablation to enter the study. They compared minimally invasive thoracoscopic pulmonary vein isolation with left atrial appendage ligation (surgical MIPI) with percutaneous catheter ablation.…”
mentioning
confidence: 99%